Ethics in public administration - Maladies and remedies - Dey, Bata K. (1995)
"After highlighting ethics-administration relationship, the author takes a brief look at developments in post-Independence administrations in India, identifying the main causes of erosion of values, and the common marks and modes of corruption in the context of development programmes. He then briefly discusses some remedial measures keeping in view the changes visualised under liberalisation"
Keywords: Civil service ethics - India; Public administration - India; Public administration